Pengembangan Antena Bowtie 2,1 GHz Terintegrasi Artificial Magnetic Conductor (AMC) untuk Aplikasi Antena Transmitter pada Sistem Ground Penetrating Radar (GPR) - Levy Olivia Nur; Raeida Widyananda; Heroe Wijanto (Jurnal Rekayasa Elektrika, 2020)
This study presented the development of the bowtie antenna system design as the transmitter in the Ground Penetrating Radar (GPR) system. The Artificial Magnetic Conductor (AMC) reflector was integrated into the antenna system as a ground plane to obtain a high gain, increase bandwidth and produce a low-profile antenna. The antenna is designed to work at a center frequency of 2.1 GHz with a range of 1.6 - 2.6 GHz and has ultrawideband (UWB) characteristics with a fractional bandwidth of ≥ 25%. In addition, the value of late-time ringing must also be reduced to -30 dB to prevent masking effects on the detected object. Antenna modeling and simulation was done to obtain the optimum prototype design. Bowtie antenna realization was carried out using RT Duroid 5880 as a substrate with dielectric constant (εr) = 2.2 and thickness (h) = 1.57 mm. The AMC reflector was fabricated with FR-4 Epoxy substrate with a dielectric constant (εr) = 4.4 and thickness (h) = 1.6 mm. The antenna realization results show that the antenna has bandwidth = 510 MHz, return loss = -15.17 dB and VSWR = 1.15. The AMC integrated bowtie antenna radiation pattern produces a unidirectional pattern with gain = 4.2 dB. However, the ringing level becomes high by -19.18 dB. Further development is needed to achieve ringing level values   that meet the GPR antenna system specifications.